Korelasi kemampuan komunikasi matematik dengan kemampuan pemecahan masalah matematik terhadap peserta didik melalui model pembelajaran Logan Avenue Problem Solving (LAPS)-Heuristic - Mentari Dewi Selvia; Satya Santika; Ipah Muzdalipah (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2017)
This study aims to determine the ability of mathematical communication and mathematical problem-solving ability to learners after using the learning model Logan Avenue Problem Solving (LAPS) -Heuristic and correlation between mathematical communication ability with mathematical problem solving ability to learners using model of learning LAPS-Heuristic. The population of the study were students of class VII of SMP Negeri 8 Tasikmalaya. Samples were taken one class at random and the selected ones were class VII I. Data collection techniques used were the provision of mathematical communication ability test and mathematical problem solving ability. Statistical analysis used is hypothesis test. The results of the analysis show the mathematical communication ability of the learners through the learning model LAPS–Heuristic baik and mathematical problem solving ability of learners through LAPS-Heuristic less good model. There is a correlation between mathematical communication ability with problem solving ability of mathematic learners using learning model LAPS-Heuristic.Keywords: Mathematical Communication, Mathematical Problem Solving, Logan Learning Model Avenue Problem Solving (LAPS) -Heuristic.